SUBCLINICAL BOVINE MASTITIS IN MUZAFFAR GARH DISTRICT OF PUNJAB (PAKISTAN) - H. A. Bachaya; M. A. Raza; S. Murtaza; I. U. R. Akbar (Journal of Animal and Plant Sciences, 2011)
The present study was carried out to determine the quarter-wise and animal-wise prevalence of sub-clinical mastitis in crossbred cows in four tehsils i.e., Muzaffar Garh, Kot Addu, Ali pur and Jatoi of District Muzaffar Garh of Punjab. Milk samples were collected from apparently mastitis free 2000 quarters of 500 crossbred cows. The samples were subjected to Surf Field Mastitis Test (SFMT). The overall quarter-wise prevalence was 35.25% while animal-wise prevalence was 36%. The maximum quarter-wise prevalence was found to be 9% in tehsil Jatoi followed by 7, 8 and 7.8% in the tehsils Muzaffar Garh, Kot Addu, and Ali pur, respectively. While the maximum animal-wise prevalence was 60% in tehsil Jatoi followed by 48, 41.6 and 30.4% in the tehsils Muzaffar Garh, Kot Addu and Ali pur, respectively.
Keywords: crossbred cows; sub-clinical mastitis; Surf Field Mastitis Test